Implementing Virtual Reality and the Metaverse to Preserve the Culture of the Baileo Negeri Rutong House, Maluku - Patty, Joanna Cristy; Valensya Yeslin Tomasoa; Lowry Hahijary (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research was conducted to introduce the Baileo Traditional House of Negeri Rutong, located in Ambon City, Maluku Province, which holds significant philosophical, religious, historical, and cultural values. Maluku, one of the provinces in Indonesia, is rich in diverse cultural heritage, including the philosophy of the Baileo Traditional House in Negeri Rutong. Baileo is a traditional communal house in Maluku, playing a central role in the local community's life. This traditional house needs to be preserved so that it can become a world attraction and a valuable cultural heritage for future generations. The purpose of this research is to develop Virtual Reality (VR) and the Metaverseas suitable media to introduce the Baileo traditional house to the world and to study the effectiveness of these media in preserving and conserving the traditional house. A design-based approach is used in this research to ensure that the development of VR and the Metaverse is conducted properly and effectively. The research stages include problem identification and needs assessment, planning and design, system development, evaluation and implementation, as well as maintenance and further development.